Open Method of Coordination in the European Union: A Trojan Horse - But who is the rider? - Peter Herrmann (Social Work and Society, 2006)
There seems to be another spectre in Europe, this time it has a little bit of a hydra. The original name was «governance», seemingly a new born child, supposedly the successor of «governing». The parents seem to be a large E, standing for Europe and a U, meaning Union. And there are children, living directly together with the parents - the many EU-committees, hearings and other bodies which claim to make EUrope open to all. And other of these children can be found in the member states, some of them being closely linked to their EUropean kin. They all reject the old-style idea of government, which they see as «closed shop of experts and technocrats». Instead, they aim on governance , a stakeholder society in which all those who have their stakes in the game should have a voice accordingly.